2019
DOI: 10.3390/bios9040134
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of an Aptamer Directed against 25-Hydroxyvitamin D for the Development of a Competitive Aptamer-Based Assay

Abstract: Detection of the small molecule 25-hydroxyvitamin D (25(OH)D) as the most relevant marker for vitamin D supply suffers from a high variability of results using the current detection methods, such as high-performance liquid chromatography (HPLC) and immunoassays. A new detection approach using a highly specific aptamer directed against 25(OH)D was established in this study based on the target-induced dissociation (TID) sensing approach. In this work, the aptamer was investigated regarding its structural propert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 28 publications
0
19
0
Order By: Relevance
“…Lee et al demonstrated the ability of a TID-based AU-NP aptasensor to monitor the small molecule hydroyvitamin D3 (25(OH)D 3 ) in the micromolar range [ 33 ]. These findings could be verified and further extended by the introduction of Cy5-labelled complementary oligonucleotides [ 34 ].…”
Section: Aptasensorsmentioning
confidence: 89%
“…Lee et al demonstrated the ability of a TID-based AU-NP aptasensor to monitor the small molecule hydroyvitamin D3 (25(OH)D 3 ) in the micromolar range [ 33 ]. These findings could be verified and further extended by the introduction of Cy5-labelled complementary oligonucleotides [ 34 ].…”
Section: Aptasensorsmentioning
confidence: 89%
“…To demonstrate the capability of the sensor system for biosensing applications, we demonstrate the detection of 25-hydroxyvitamin D (25OHD) as a model analyte from diluted serum samples. Since 25OHD is a relatively small molecule and thus only induces a relatively small refractive index change above the SPR sensor surface, a competitive aptamer-based assay recently developed by our team [18], was applied. In this assay, a DNA aptamer [19] directed against 25OHD is used in combination with an oligonucleotide that is complementary to a section of the aptamer which is involved in binding of the aptamer target.…”
Section: Sensor Designmentioning
confidence: 99%
“…In the absence of the target, the oligonucleotide forms a duplex with the aptamer, while in the presence of 25OHD, the aptamer binds to its target instead. Through this process, the binding of the small molecule 25OHD, which is hard to detect by SPR in general, is translated into the dissociation of the larger oligonucleotide [18]. To further increase the 25OHD-induced changes of the refractive index above the sensor surface, gold nanoparticles (AuNPs) were used for signal enhancement, as described recently for aptamer-based detection of CRP [17].…”
Section: Sensor Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, by incorporating these nucleic acid aptamers into various sensing platforms, it is possible to subject these probes to repeated use without loss of functionality, thereby allowing a device to be potentially recyclable. Numerous aptamer-based approaches have been reported for chemical and biological detection, such as surface-enhanced Raman spectroscopy [40,41], SPR [42,43], fluorescence [44,45], colorimetry [46,47], and electrochemistry [48,49].…”
Section: Introductionmentioning
confidence: 99%